Gibalna učinkovitost mestnih, primestnih in podeželskih otrok - Matejek, Črtomir; Planinšec, Jurij (Revija za elementarno izobraževanje, 2008)
The Physical Efficiency of Children from Urban, Suburban and Rural Areas. The main aim of the research was to find out whether there are any differences in physical fitness between children from urban, suburban and rural areas. The research was carried out on 451 children, aged from six to nine years. Among these children, 176 were from urban areas, 147 from suburban areas and 128 from rural areas. The children were from three different elementary schools in the northeastern part of Slovenia. In order to assess their physical fitness levels, six different tests were given in the following categories: explosive power, balance, visualmotor coordination, speed of alternate movements, whole-body coordination and endurance. The ANOVA method was used to asses the differences in physical fitness levels between children from different backgrounds. The statistical significance level was set at p
Keywords: children; motor development; physical activity; physical fitness; living environment